Application of hydrogeochemistry and isotopic characterization for the assessment of recharge in a volcanic aquifer in the eastern region of central Costa Rica. - Madrigal-Solís, Helga; Jiménez-Gavilán, Pablo; Vadillo-Pérez, Iñaki; Fonseca-Sánchez, Alicia; Quesada-Hernández, Luis; Sánchez-Gutiérrez, Rolando; Calderón-Sánchez, Hazel; Pardo-Vargas, Carlos (Taylor & Francis, 2020)
In the eastern region of central Costa Rica, land use in the sub-basins of the Maravilla-Chiz and Quebrada Honda rivers (47 km2) is dominated by agricultural and livestock production, while groundwater resources constitute the main drinking water supply. This study aimed to (a) evaluate the location of groundwater recharge areas and groundwater flow paths, and (b) provide a characterization of the hydrochemistry and possible anthropic impacts. Groundwater was collected from 20 sites during the dry and rainy seasons and analysed for major ions, water stable isotopes and 222Rn. Approximated recharge areas were estimated through a local altitudinal line based on isotopic compositions in springs. The hydrochemical and isotopic characterization of groundwater showed that the main recharge areas occur in the upper part of the basin, except for springs in the middle part of the basin probably due to a certain hydraulic disconnection from the upper part that facilitates local recharge processes. In the lower basin, groundwater exhibited greater transit times and longer flow paths. Low nitrate, chloride and sulphate concentrations found in groundwater indicate low leaching of fertilizers or urban wastewaters. Our results are focused to improve water resources and agricultural management plans in a dynamic tropical landscape.
https://openpolicyfinder.jisc.ac.uk/id/publication/5477
Keywords: Química del agua - Costa Rica; Acuíferos - Costa Rica; Altitudinal recharge line; Costa Rica; Groundwater recharge; Hydrochemistry; Hydrogen-2; Isotope hydrology; Oxygen-18; Principal components analysis; Radon-222; Water quality